LYRA GRAECA - Edmonds, J.M. (edición) (1952)
CONTENIDO: V. 1 TERPANDER ALCMAN SAPPHO AND ALCAEUS. -- V.2 STESICHORUS IBYCUS ANACREON AND SIMONIDES. -- V. 3 CORINNA BACCHYLIDES TIMOTHEUS THE ANONYMOUS FRAGMENTS THE FOLK-SONGS AND THE SCOLIA WITH AN ACCOUNT OF GREEK LYRIC POETRY